Spatial distribution of migratory Salmo trutta in the northern Baltic Sea - Kallio-Nyberg, Irma; Veneranta, Lari; Saloniemi, Irma; Jutila, Eero; Pakarinen, Tapani
Spatial distribution of brown trout (Salmo trutta) was studied on the Finnish coast of the northern Baltic Sea in 1998–2010 based on smolt tagging. The studied trout stocks were hatchery reared, and smolts were tagged with Carlin tags before release into the rivers. The distance between the release and recapture sites as well as location of the recapture site in relation to the release site (north, south, west, east) were analysed, taking the stock and sea age of the trout into account. The most important tag recovery areas at sea were the estuaries of the spawning rivers and coastal areas surrounding them. The natural direction of movement was along the coast line, north or south on the western coast and east or west in the Gulf of Finland. The release site and age affected migration direction. The distance of recoveries from the release sites varied for the same genetic stock released at different sites. The longest median recapture distances were recorded during the second sea year. The stocked brown trout (80%–95%) were mainly caught during their first two years in the sea before they become mature. Knowledge of spatial dispersal of sea trout is important for the management of the stocks and fisheries. 2017